What to watch when : 1,000 TV shows for every mood and moment - Blauvelt, Christian; Buller, Laura, 1952-; Frisicano, Andrew; Grant, Stacey; Morris, Mark, 1963-; Robson, Eddie; Serota, Maggie; Toal, Drew; Turner, Matthew (Film critic); Ulster, Laurie (DK Publishing, 2020)
"Answering the eternal question... WHAT TO WATCH NEXT? Looking for a box set to get your adrenaline racing or to escape to a different era? In need of a good laugh to lift your spirits? Hunting for a TV show that the whole family can watch together? If you're feeling indecisive about your next binge-watching session, we've done the hard work for you. Featuring 1,000 carefully curated reviews written by a panel of TV connoisseurs, What To Watch When offers up the best show suggestions for every mood and moment."--From publisher.